Open Access Journals: The Nuts and Bolts Experience of ECU Faculty - Kester, Diane D.; Steinweg, Sue; Yang, Biwu (East Carolina University, 2009)
Editors of the Journal of Curriculum and Instruction discuss their experiences starting up an open access journal using the open journal system.
Keywords: Open access; Journal of curriculum and instruction; Open journal system